Meningkatan keterampilan siswa dengan pembelajaran Project Based Learning pada pembelajaran IPAS materi kekayaan budaya Indonesia - Oktina Dwi Prastyani; Wahyu Kurniawati; Henry Aditia Rigianti (Borobudur Educational Review, 2023)
Student-centered learning can build students' skills, creativity and activeness in the learning process in the classroom. This is the key to learning in the classroom. The Project Based Learning Learning Model is a learning strategy where students must use thoughts, ideas and creativity so that they can improve students' skills in learning science and science by creating a Map of Indonesian Cultural Diversity. In this research, the results of this research show that the Project Based Learning model using the Diversity Map can be positively successful as seen from the students' enthusiasm when learning.